Brain atrophy patterns in multiple sclerosis patients treated with natalizumab and its clinical correlates. Issue 5 (10th April 2022) - Rekik, Arwa; Aissi, Mona; Rekik, Islem; Mhiri, Mariem; Frih, Mahbouba Ayed
Abstract: Background: Multiple sclerosis (MS) is defined as a demyelinating disorder of the central nervous system, witnessing over the past years a remarkable progress in the therapeutic approaches of the inflammatory process. Yet, the ongoing neurodegenerative process is still ambiguous, under‐assessed, and probably under‐treated. Atrophy and cognitive dysfunction represent the radiological and clinical correlates of such process. In this study, we evaluated the effect of one specific MS treatment, which is natalizumab (NTZ), on brain atrophy evolution in different anatomical regions and its correlation with the cognitive profile and the physical disability. Methods: We recruited 20 patients diagnosed with relapsing‐remitting MS (RR‐MS) and treated with NTZ. We tracked brain atrophy in different anatomical structures using MRI scans processed with an automated image segmentation technique. We also assessed the progression of physical disability and the cognitive function and its link with the progression of atrophy. Results: During the first 2 years of treatment, a significant volume loss was noted within the corpus callosum and the cerebellum gray matter (GM). The annual atrophy rate of the cortical GM, the cerebellum GM, the thalamus, the amygdala, the globus pallidus, and the hippocampus correlated with greater memory impairment. As for the third and fourth years of treatment, a significant atrophy revolved around the gray matter, mainly the cortical one. We also noted an increase of the thalamus volume. Conclusion: Atrophy in RR‐MS patients treated with NTZ is regional and targeting highly cognitive regions mainly of the subcortical gray matter and the cerebellum. The cerebellum atrophy was a marker of physical disability progression. NTZ did not accelerate the atrophy process in MS and may play a neuroprotective role by increasing the thalamus volume. Abstract : This study demonstrated the regional and dynamic aspect of atrophy progression in multiple sclerosis patients treated with natalizumab and its correlations with both physical disability and cognitive impairment. It also highlighted the effect of such treatment of the thalamus, suggesting a potential neuroprotective role.